2021
DOI: 10.3389/pore.2021.1609922
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Intra-Tumoral Vaccinations of Quadrivalent HPV-L1 Peptide Vaccine With Topical TLR-7 Agonist Following Recurrence: Complete Resolution of HPV-HR-Associated Gynecologic Squamous Cell Carcinomas in Two Patients

Abstract: The human papilloma virus (HPV) high-risk variants (HPV-HR) such as HPV16 and HPV18 are responsible for most HPV related cancers, including anogenital and head and neck cancers. Here, we present two patients with HPV-HR-associated gynecological malignancies who, after failing radiation therapy, were treated with experimental salvage immunotherapy regimen resulting in complete, durable responses in both patients. Each patient was diagnosed with recurrent, radiation-refractory, HPV-HR positive, squamous cell car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…5 Although designed to be prophylactic, 2 the 9-valent HPV vaccine may also have therapeutic properties, consistent with this and other reports. 1,3,4 This treatment approach was well tolerated, effective, and improved our patient's quality of life dramatically; for patients with SCCIS of the penis who are poor surgical candidates, this may be an effective alternative treatment. Since the durability of the therapeutic response is unknown, close monitoring for recurrence is required.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…5 Although designed to be prophylactic, 2 the 9-valent HPV vaccine may also have therapeutic properties, consistent with this and other reports. 1,3,4 This treatment approach was well tolerated, effective, and improved our patient's quality of life dramatically; for patients with SCCIS of the penis who are poor surgical candidates, this may be an effective alternative treatment. Since the durability of the therapeutic response is unknown, close monitoring for recurrence is required.…”
mentioning
confidence: 85%
“…Four doses of the 0.5 ml 9-valent HPV were administered undiluted intralesionally on 09/27/2019, 12/05/2019, 01/16/2020, and 03/10/2021. The patient experienced resolution without side effects and has not had a clinical recurrence in 20 months (Figure 2c,d).HPV is responsible for approximately 30% of viral-induced cancers 1. In the development of SCCIS of the penis, b-HPV subtypes 16 and 18 are the most common 2.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Patients with central recurrence of cervical cancer receive at least two intratumoral Gardasil injections and local injection of imiquimod on the tumor surface. The addition of a combination of local TLR7 agonist therapy on the basis of intratumoral vaccination can unexpectedly lead to complete regression of the disease in two patients ( 113 ). Due to the potential lack of immunogenicity of peptides themselves, it is widely believed that standard/conventional vaccine adjuvants may not provide the intense inflammatory signals required to provoke specific responses against peptide pointed at treatment tumor vaccines.…”
Section: Treatment Of Hpv Related Cancersmentioning
confidence: 99%
“…It has been known that radiation therapy induces immunogenic cell death to generate tumor antigens and improves antigen presentation efficiency. Clinical studies [ 70 ] have demonstrated that proton-beam radiotherapy combined with in situ vaccine is safe and feasible for patients with hepatocellular carcinoma. The first clinical trial conducted by Abei et al .…”
Section: Introductionmentioning
confidence: 99%